Bioplastic degradation by a polyhydroxybutyrate depolymerase from a thermophilic soil bacterium. (26th October 2022) - Thomas, Gwendell M.; Quirk, Stephen; Huard, Dustin J. E.; Lieberman, Raquel L.
Abstract: As the epidemic of single‐use plastic worsens, it has become critical to identify fully renewable plastics such as those that can be degraded using enzymes. Here we describe the structure and biochemistry of an alkaline poly[( R )‐3‐hydroxybutyric acid] (PHB) depolymerase from the soil thermophile Lihuaxuella thermophila . Like other PHB depolymerases or PHBases, the Lihuaxuella enzyme is active against several different polyhydroxyalkanoates, including homo‐ and heteropolymers, but L. thermophila PHB depolymerase ( Lt PHBase) is unique in that it also hydrolyzes polylactic acid and polycaprolactone. Lt PHBase exhibits optimal activity at 70°C, and retains 88% of activity upon incubation at 65°C for 3 days. The 1.2 Å resolution crystal structure reveals an α/β‐hydrolase fold typical of PHBases, but with a shallow active site containing the catalytic Ser‐His‐Asp‐triad that appears poised for broad substrate specificity. Lt PHBase holds promise for the depolymerization of PHB and related bioplastics at high temperature, as would be required in bioindustrial operations like recycling or landfill management. Abstract : PDB Code(s): 8DAJ